Structural and genetic analyses of glycan O-acetylation in a bacterial protein glycosylation system: evidence for differential effects on glycan chain length - Anonsen, Jan Haug; Børud, Bente; Vik, Åshild; Viburiene, Raimonda; Koomey, Michael (Glycobiology (Oxford), 2017)
O-acetylation is a common modification of bacterial glycoconjugates. By modifying oligosaccharide structure and chemistry, O-acetylation has important consequences for biotic and abiotic recognition events and thus bacterial fitness in general. Previous studies of the broad-spectrum O-linked protein glycosylation in pathogenic Neisseria species (including N. gonorrhoeae and N. meningitidis) have revealed O-acetylation of some of their diverse glycoforms and identified the committed acetylase, PglI. Herein, we extend these observations by using mass spectrometry to examine a complete set of all glycan variants identified to date. Regardless of composition, all glycoforms and all sugars in the oligosaccharide are subject to acetylation in a PglI-dependent fashion with the only exception of di-N-acetyl-bacillosamine. Moreover, multiple sugars in a single oligosaccharide could be simultaneously modified. Interestingly, O-acetylation status was found to be correlated with altered chain lengths of oligosaccharides expressed in otherwise isogenic backgrounds. Models for how this unprecedented phenomenon might arise are discussed with some having potentially important implications for the membrane topology of glycan O-acetylation. Together, the findings provide better insight into how O-acetylation can both directly and indirectly govern glycoform structure and diversity.